A LIBERATIVE APPROACH TO ISSUES OF MUSLIM WOMEN IN INDIA - Engineer, Asghar Ali (Journal of Dharma, 2009)
It is a fact that many Muslim women in India lack empowerment and experience grinding poverty, illiteracy, and various restrictions imposed on them by their parents and husbands in their everyday life. When I deliver lectures on rights of women in Islam, participants invariably ask me about the actual plight of women in Muslim society today. I have to offer a lot of explanation as to the reasons of their sad plight. There are certain factors for which Muslims cannot be blamed like poverty. There are, however, certain other factors for which Muslims have to own responsibility like imposing restrictions exclusively upon women, which have nothing to do with Islam. These restrictions are rooted more in social customs and traditions of the past but legitimised in the name of Shari’ah.